Priority tendencies in political communication (Herald of Journalism, 2019)
This article analyzes the place and role of the media in today’s political communication. It is known that modern digital technologies are one of the main instruments for implementing any policy. The pur-pose of the article is to determine the types and categories of the concept of this impact in the modern globalization space. Also views and opinions of various scientists are considered. The terms “communi-cation” and “information” are descriptive in nature and are determined on the basis of specific research results. They are defined in the categories of political activity and political communication. K. Shannon, N. Wiener and others view the theory of entropy as a balance between human aspiration and natural processes. Forms of political communication in terms of “political education” and “political activity” are interpreted. An overview of the current functioning of the media in the political space and its prior-ity trends is given. To achieve the goal of the study, the methods of generalization, classification of the revealed patterns, analysis were applied. Summarizing all the information mentioned above, the authors of the article come to the conclusion that theories introduced into the field of political communication studies sometimes lead to difficulties in the course of a methodological study. In addition, modern research in the field of political communica-tion, as well as any other emerging field of knowledge, has not yet been freed from controversial views on some fundamental problems.
Keywords: communications, media, politics, process, information, category.